Effect of different storage periods on pathogenic bacteria isolated from wheat grains contaminated with serrated grain beetle Oryzaephilus surinamensis L. (Coleoptera: Silvanidae) stored in Al-Rifai city - AL-Shwelly, Ashjan Agar Nasser (Technium BioChemMed, 2024)
The study was carried out in the College of Science, University of Sumr, an insect lab during the year 2022. The current study was conducted to isolate and diagnose some types of aerobic pathogenic bacteria during different time periods 3 months, 6 months and 9 months from wheat grains infected with the serrated grain beetle and to know the effect of changing the periods on the level of contamination with pathogenic bacteri Nine types of pathogenic bacteria have been isolated (Bacillus cereus, Escherichia coli , Proteus mirabils , Enterococcus faecalis , Enterobactor aerogenes , Pseudomonas aerugenosa, Klebsiella pneumonia, Staphlococcus aureus, Staphlococcus epidermidis) from mechanically damaged wheat samples infected with the insect under the influence The factor of the difference in the duration of storage, and it was found that the period of 6 months is relatively superior.